2019
DOI: 10.7150/ntno.35935
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming hypoxia-induced chemoresistance to cisplatin through tumor oxygenation monitored by optical imaging

Abstract: Perfluorocarbon nanoparticles have been reported to deliver oxygen to tumors and reduce hypoxia-induced radioresistance, however few studies have been carried out to study its role in reducing hypoxia-induced chemoresistance. The oxygenation effect also varies dramatically between different perfluorocarbon formulations and protocols, and there have been no efficient tools to monitor dynamic changes of tumor oxygenation non-invasively. Our goal was to promote tumor oxygenation using perfluorooctyl bromide (PFOB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…However, p53 knockdown did not modulate resistance to cisplatin (66). A preoxygenated perfluorooctyl bromide (PFOB) nanoemulsion with carbogen breathing effectively increased tumor oxygenation in mouse model, which associated with an increase in cisplatin-mediated apoptosis of cancer cells and inhibition of tumor growth with low doses of cisplatin treatment (67).…”
Section: Discussionmentioning
confidence: 99%
“…However, p53 knockdown did not modulate resistance to cisplatin (66). A preoxygenated perfluorooctyl bromide (PFOB) nanoemulsion with carbogen breathing effectively increased tumor oxygenation in mouse model, which associated with an increase in cisplatin-mediated apoptosis of cancer cells and inhibition of tumor growth with low doses of cisplatin treatment (67).…”
Section: Discussionmentioning
confidence: 99%
“…The initial idea of oxygen therapy for cancer treatment using ozone or hydrogen peroxide, decomposing into oxygen, dates back decades ago [30][31][32][33][34][35][36][37]. Later studies have also shown beneficial effects of oxygen therapy in some cancers [9,[38][39][40][41]. For example, it has been shown that the effect of chemotherapy is significantly increased immediately after hyperbaric oxygen therapy [42].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the oxygen-absorbed PFTBA@HSA NPs possess two-stage oxygen delivery, that is, oxygen evaporation from PFTBA as the first stage and elevated RBC infiltration as the second stage, which was demonstrated to be effective in reliving the hypoxic level ( Zhou et al, 2018a ; Zhou et al, 2018b ). In addition to the PFTBA, some other PFC derivatives such as Perfluoropentane (PFP) ( Chen S. et al, 2018 ) and Perfluorooctylbromide (PFOB) ( Song et al, 2019 ), are also good oxygen carriers, which have been studied to relieve tumor hypoxia ( Table 4 ).…”
Section: Oxygen-based Nanocarriers To Relieve Tumor Hypoxiamentioning
confidence: 99%
“…Results from their study revealed that hypoxia could be alleviated at a moderate rate and the intracellular EP level was significantly elevated, thus effectively decreasing the hypoxia-induced CMT resistance. Similarly, PFOB nanoemulsion has proven to have great potential to overcome hypoxia-induced cisplatin resistance ( Song et al, 2019 ). PFTBA-based HSA NP capable of enhancing oxygen carrier RBC distribution in tumor site was originally engineered by Zhou et al (2018b) , which significantly amplified CMT efficacy with in vivo TGI of more than 80% by improving tumor oxygen concentration.…”
Section: Oxygen-based Nanocarriers To Enhance Tumor Therapiesmentioning
confidence: 99%